The Contribution of Nutrition in Compression Therapy for Chronic Venous Disease - Yuwono, Hendro Sudjono; Pratama, Dedy (British Journal of Healthcare and Medical Research, 2020)
Compression therapy is an essential step for the treatment of chronic venous disease (CVD). It is a mechanical treatment against the venous wall's persistent pathological change and the CVD created by inner metabolic substances that damage the wall and valves. The damage is possible to prevent using flavonoid drug and daily nutrition intake, which support the mechanical therapy positively.